Seasonal predictability of wintertime windstorm climate over the North Atlantic and Europe : Saisonale Vorhersagbarkeit von Wintersturmklima in der Region Nordatlantik und Europa - Renggli, Dominik (Freie Universität Berlin, 2011)
Abstract iii Zusammenfassung v 1 Introduction 1 1.1 Windstorms in the North Atlantic and European region . . . . . . . . . . . 1 1.1.1 Physical basis . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 1 1.1.2 Impacts of European windstorms . . . . . . . . . . . . . . . . . . . 2 1.2 Seasonal forecasting . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 4 1.2.1 A short history of seasonal forecasting . . . . . . . . . . . . . . . . 4 1.2.2 Physical basis of seasonal forecasting . . . . . . . . . . . . . . . . . 8 1.3 Motivation of the thesis . . . . . . . . . . . . . . . . . . . . . . . . . . . . 17 1.3.1 Seasonal windstorm predictability: a review . . . . . . . . . . . . . 17 1.3.2 Potential use of seasonal windstorm risk predictions . . . . . . . . . 20 1.3.3 Objectives of the thesis . . . . . . . . . . . . . . . . . . . . . . . . . 21 1.3.4 Outlines of the thesis . . . . . . . . . . . . . . . . . . . . . . . . . . 23 2 Data 25 2.1 Reanalysis data . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 25 2.2 Observational data . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 26 2.3 Seasonal prediction model data: DEMETER and ENSEMBLES . . . . . . 27 2.4 Growth factors of extra-tropical cyclones . . . . . . . . . . . . . . . . . . . 30 3 Deﬁnition and identiﬁcation of windstorms 31 3.1 Rational . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 31 3.2 Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 32 3.2.1 Tracking scheme . . . . . . . . . . . . . . . . . . . . . . . . . . . . 32 3.2.2 Storm Severity Index . . . . . . . . . . . . . . . . . . . . . . . . . . 35 3.3 Climatology in reanalysis data . . . . . . . . . . . . . . . . . . . . . . . . . 35 3.4 Sensitivity on tracking parameters . . . . . . . . . . . . . . . . . . . . . . . 38 3.5 Relation to growth factors of cyclones . . . . . . . . . . . . . . . . . . . . . 41 3.6 Conclusions . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 44 4 Potential sources of wintertime windstorm predictability over the North Atlantic and Europe on seasonal time scales 45 4.1 Rational . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 45 4.2 Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 47 4.2.1 Wintertime windstorm climate . . . . . . . . . . . . . . . . . . . . . 47 4.2.2 Lead-Lag-Correlation and partial correlation . . . . . . . . . . . . . 47 4.2.3 Composites of years with strong HF anomalies . . . . . . . . . . . . 48 4.3 Relation between hemispheric-scale factors and windstorm climate . . . . . 49 4.3.1 Correlation patterns . . . . . . . . . . . . . . . . . . . . . . . . . . 49 4.3.2 Lead-Lag-Correlation . . . . . . . . . . . . . . . . . . . . . . . . . . 50 4.3.3 Inter-dependencies between hemispheric-scale factors . . . . . . . . 54 4.4 Possible physical mechanisms on seasonal time scales . . . . . . . . . . . . 55 4.4.1 NAO as precursor of the North Atlantic Horseshoe . . . . . . . . . 56 4.4.2 The role of the North Atlantic Horseshoe pattern . . . . . . . . . . 59 4.5 Conclusions . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 61 5 Predictive skill in seasonal ensemble prediction systems to forecast win- tertime wind storm climate 65 5.1 Rational . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 65 5.2 Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 67 5.2.1 Deﬁnition and identiﬁcation of wintertime windstorm . . . . . . . . 67 5.2.2 Measures of predictive skill . . . . . . . . . . . . . . . . . . . . . . . 68 5.2.3 Relation between predictive skill and windstorm frequency . . . . . 70 5.3 Windstorms in reanalysis and seasonal hindcast data . . . . . . . . . . . . 71 5.4 Predictive skill . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 74 5.5 Some aspects of the variability of skill . . . . . . . . . . . . . . . . . . . . . 79 5.6 Conclusions . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 83 5.7 Appendix . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 85 6 Sources of skill in seasonal prediction models forecasting North Atlantic and European wintertime windstorms 87 6.1 Rational . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 87 6.2 Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 90 6.2.1 Hemispheric-scale factors . . . . . . . . . . . . . . . . . . . . . . . . 90 6.2.2 Composite analysis . . . . . . . . . . . . . . . . . . . . . . . . . . . 91 6.3 Relation of anomalous hemispheric-scale factors to windstorm occurrence . 93 6.3.1 North Atlantic SST Horseshoe . . . . . . . . . . . . . . . . . . . . . 93 6.3.2 Continental snow cover extent . . . . . . . . . . . . . . . . . . . . . 103 6.4 Sources of predictive skill in forecasting wintertime windstorm occurrence . 104 6.4.1 Persistence of oceanic anomalies from August to November hindcasts105 6.4.2 NAO and continental snow cover as additional sources of skill? . . . 112 6.4.3 The link to predictive skill . . . . . . . . . . . . . . . . . . . . . . . 114 6.5 Conclusions . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 115 7 Synthesis 117 7.1 Summary . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 117 7.2 Discussion and Conclusions . . . . . . . . . . . . . . . . . . . . . . . . . . 119 7.3 Potential applicability of the results . . . . . . . . . . . . . . . . . . . . . . 129 Bibliography 133 Acknowledgments 151 : Strong extra-tropical cyclones are a characteristic feature of mid-latitudinal weather. In extreme cases, such cyclones are accompanied by severe wind speeds. These windstorms are the natural hazard with the highest loss potential in the North Atlantic and European region. Thus, prediction of windstorm climate on seasonal time scales would be beneﬁcial for society and economy. However, the skill of seasonal predictions of wintertime windstorm occurrence and its sources have not been extensively analyzed. Therefore, this thesis addresses the following issues: a) How can windstorms be objectively identiﬁed? b) Which factors are related to wintertime windstorm occurrence on seasonal time scales in observational data, and may therefore be considered as potential sources of seasonal predictability? c) Do state-of-the-art dynamical seasonal prediction models successfully forecast windstorm climate? d) Which factors inﬂuence the occurrence of windstorm in such prediction models, i.e., what are the sources of predictive skill? To this end, an impact-based, objective windstorm identiﬁcation scheme is developed based on surface wind speeds exceeding the local 98th percentile in consecutive timesteps. The scheme can be applied to both reanalysis products and climate (prediction) model data. It is shown to successfully identify individual historical events. Furthermore, both the spatial and temporal climatologies of the identiﬁed events are in good agreement with observations. Windstorms identiﬁed in reanalysis data are used to analyze their relationship to observed anomalies of hemispheric-scale factors such as North Atlantic sea surface temperature and sea ice, continental snow cover extent, and the North Atlantic Oscillation. The correlation between anomalies of these factors in summer and autumn and the windstorm occurrence in subsequent winter (i.e., with a lead time of four to six months) is statistically signiﬁcant with coefficients of up to 0.43. Hence, hemispheric-scale factors explain at least 20% of the inter-annual variability of windstorm climate. A composite study reveals that an anomalous state of the North Atlantic Oscillation in summer supports the generation of speciﬁc temperature anomalies in the North Atlantic ocean in autumn, namely the North Atlantic Horseshoe pattern. These anomalies persist until winter and induce anomalous growth conditions for extra-tropical cyclones over the North Atlantic (e.g., increased baroclinicity in areas of increased meridional temperature gradients, or increased latent heat over areas of positive sea surface temperature anomalies). Such conditions are favorable for the development of strong cyclones, and therefore potentially a higher number or stronger wintertime windstorms in the North Atlantic and European region. Such physically motivated links between anomalies in the North Atlantic Ocean, their persistence and their impacts on growth conditions of cyclones are potential sources of windstorm predictability on the seasonal time scale. The windstorm identiﬁcation scheme is also applied to data of the DEMETER and ENSEMBLES projects. These data consist of seasonal hindcasts produced by several coupled ocean-atmosphere climate models. December–February windstorm frequency in the 1980–2001 period is statistically signiﬁcantly predicted by the multi-model ensembles and several single-model ensembles with a lead time of one to three months, with skill ranging between 0.10–0.40. The 1980–2001 period is shown to be generally better predictable than the 1960–1980 period. Additionally, the winters with high windstorm frequency are better predicted than winters with average storm counts. The sources of predictive skill in these model ensembles are investigated by quantifying the relation between hemispheric-scale factors, growth factors of cyclones, and windstorm occurrence in the prediction models. The relation between hemispheric-scale factors and wintertime windstorms is weaker than in observations and insigniﬁcant on the seasonal time scale. Still, composites of hindcast runs with strong North Atlantic Horseshoe anomalies reveal similar relations to growth factors as found in observations. However, the persistence of the oceanic anomalies is very different in the individual models, and generally weaker than in observations, probably related to deﬁciencies in the coupling between ocean and atmosphere in the prediction models. The preservation of oceanic anomalies in the models’ ocean control run from summer until the onset of the hindcasts started in November is shown to be a crucial factor for predictive skill. Models able to retain such anomalies in closer agreement with observations develop stronger anomalies in sea surface temperature, growth factors of cyclones, and windstorms, and show higher skill scores. Therefore, it is argued that the North Atlantic is one source of predictive skill for seasonal windstorm predictions, and that improvements of the ocean-atmosphere coupling in prediction models could enhance skill. : Tiefdruckgebiete sind ein charakteristisches Merkmal des Wetters der Mittleren Breiten. Starke Tiefdruckgebiete im Winter sind oft mit extremen Windgeschwindigkeiten verbunden. Solche Winterstürme sind die schadenträchtigsten meteorologischen Extremereignisse in Europa. Diesbezügliche Vorhersagen auf der saisonalen Skala sind deshalb von gesellschaftlichem und wirtschaftlichem Interesse. Über die Vorhersagbarkeit von Wintersturmaktivität auf der saisonalen Skala und ihre Quellen ist allerdings wenig bekannt. Deshalb beschäftigt sich diese Promotion mit den folgenden Fragen: Wie lassen sich Winterstürme objektiv deﬁnieren und identiﬁzieren? Welche Faktoren hängen Beobachtungsdaten zufolge mit dem Auftreten von Winterstürmen auf der saisonalen Skala zusammen und kommen somit als potentielle Quellen von Vorhersagbarkeit in Frage? Wie gut sagen aktuelle saisonale Vorhersagemodelle das Wintersturmklima vorher? Welche Faktoren beeinﬂussen in diesen Modellen die Wintersturmaktivität, d.h. was sind die Quellen der Vorhersagegüte? Winterstürme werden mit einer objektiven Identiﬁkationsmethode bestimmt. Die Methode basiert auf der Identiﬁkation von räumlich konsistenten Überschreitungen des lokalen 98. Perzentils des Bodenwindes und kann sowohl auf Reanalysen als auch auf Vorhersage- und Klimamodelle angewendet werden. Historische Winterstürme werden von der Methode erfolgreich identiﬁziert. Die zeitlichen und räumlichen Klimatologien der identiﬁzierten Ereignisse stimmen gut mit Beobachtungen überein. Das in Reanalysen identiﬁzierte Wintersturmklima wird benutzt, um dessen Zusammenhang mit beobachteten Anomalien von hemisphärisch-skaligen Faktoren wie Meeresoberﬂächentemperaturen und Meereis im Nordatlantik, kontinentale Schneebedeckung und der Nordatlantischen Oszillation auf saisonalen Zeitskalen zu untersuchen. Es zeigt sich, dass die hemisphärisch-skaligen Faktoren im Sommer/Herbst (d.h. mit Vorlaufzeiten von vier bis sechs Monaten) statistisch signiﬁkant mit der Sturmaktivität im Winter (Dezember-Februar) korrelieren. Die Korrelationskoeffizienten betragen bis zu 0.43, was einer erklärten Varianz von ungefähr 20% entspricht. Eine Kompositanalyse zeigt, dass Anomalien der Nordatlantischen Oszillation im Sommer die Entstehung des sogenannten “Horseshoe patterns”, eines hufeisenförmigen Musters von Anomalien der Meeresoberﬂächentemperaturen im Nordatlantik, im darauffolgenden Herbst begünstigt. Diese Anomalien bleiben bis zum Winter erhalten und führen zu anomalen Wachstumsbedingungen für extra-tropische Zyklonen über dem Nordatlantik (z.B. erhöhte Baroklinität in Regionen mit verstärkten meridionalen Temperaturgradienten und erhöhte Werte der latenten Wärme über positiven Anomalien der Meeresoberﬂächentemperatur). Solche Bedingungen fördern die Entwicklung von starken Zyklonen und deshalb möglicherweise auch von mehr oder stärkeren Winterstürmen über Europa. Physikalisch begründbare Zusammenhänge wie jene zwischen Anomalien im Nordatlantik, deren Persistenz und deren Einﬂuss auf Wachstumsbedingungen von Zyklonen stellen potentiellen Quellen für die saisonale Vorhersagbarkeit von Winterstürmen dar. Winterstürme werden analog zu den Reanalysen auch in den Vorhersagedaten des DEMETER und des ENSEMBLES Projekts identiﬁziert. Diese saisonalen Vorhersagen wurden von verschiedenen gekoppelten Ozean-Atmosphäre-Modellen gerechnet. Die Multi- Modell-Ensembles und gewisse Einzelmodelle zeigen statistisch signiﬁkante Güte in der Vorhersage der Wintersturmanzahl im Dezember bis Februar, mit Vorlaufzeiten von einem bis drei Monaten. Der Ranked Probability Skill Score erreicht dabei Werte von 0.10–0.40. Im Zeitraum von 1980–2001 ist die Vorhersagegüte generell besser als im Zeitraum 1960–1980. Winter mit hoher Wintersturmaktivität werden grundsätzlich besser vorhergesagt als Winter mittlerer Wintersturmaktivität. Die Quellen der Vorhersagegüte werden anhand der von den Vorhersagemodellen simulierten Zusammenhänge zwischen hemisphärisch-skaligen Faktoren, Wachstumsbedingungen für Zyklonen und Winterstürmen untersucht. Diese Zusammenhänge sind in den Modellen grundsätzlich schwächer ausgeprägt als die beobachteten Zusammenhänge. Allerdings zeigen Modellläufe mit starken Anomalien des “Horseshoe patterns” ähnliche Relationen zu Wachstumsbedingungen von Zyklonen wie die Beobachtungen. Die Persistenz dieser Anomalien ist aber in den Modellen unterschiedlich stark ausgeprägt und im Allgemeinen schwächer als die beobachtete Persistenz. Deﬁzite in der Kopplung zwischen der Ozean- und der Atmosphärenkomponente der Vorhersagemodelle sind mögliche Gründe für diese Unterschätzung. Ein entscheidender Faktor für die Vorhersagegüte eines Modells ist seine Fähigkeit, ozeanische Anomalien im Ozean-Kontrolllauf vom Sommer bis zum Start der Wintervorhersage zu speichern. Je stärker die Persistenz solcher Anomalien, desto stärker sind entsprechende Anomalien im Nordatlantik, der Wachstumsfaktoren von Zyklonen und dem Auftreten von Winterstürmen und desto besser ist im Allgemeinen die Vorhersagegüte. Dies lässt den Schluss zu, dass der Nordatlantik eine Quelle von saisonaler Vorhersagbarkeit von Winterstürmen ist. Verbesserungen der Kopplung zwischen Ozean und Atmosphäre in den Vorhersagemodellen würden dementsprechend auch bessere Vorhersagen erlauben.